FACTORS RELATED TO THE REDUCTION OF MEDICATION DISCREPANCIES AT TRANSITION OF CARE: A SYSTEMATIC REVIEW - Ida Bagus Nyoman Maharjana; Adik Wibowo (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: Adverse drug events (ADE) are a leading cause of injury and death within health care systems around the world. Up to 67% of patients’ prescription medication histories recorded on admission to hospital have one or more errors and 30 – 80% of patients have a discrepancy between the medicines ordered in hospital and those they were taking at home. This study aims to systematically evaluate the available literature on the medication history records as a quality improvement in reducing medication discrepancies during the transition of care. Methods: This study was used systematic review which performed according to the PRISMA method. The search included articles were obtained through databases: MEDLINE (1946), EMBASE (1966), CINAHL (1937) and PubMed (1946). Some of the key words or Medical Subject Heading (MeSH) terms used in the search were: “transition of care,” “medication discrepancies,” “medication errors,” “patient safety,” “medication history,” “patient admission,” “patient discharge,” “patient transfer,” and “hospital”. Only studies published in English were included. Exploring literature was focused on the articles published from 2009 to 2019. Results: Initially, a total of 162 potentially relevant articles were obtained. After screening tittle and reviewing abstracts, 14 full text were assessed for eligibility. Of the 10 articles met all inclusion criteria, 5 studies were randomized controlled trials, 2 quasi-experimental studies, 1 cohort study, and 2 qualitative studies with quantitative approaches. All studies found that involving best possible medication history in identifying medication discrepancies and communicating this information affected medication discrepancies in the medical record. Conclusions: The available literature such as lack of well-designed studies precluded us from concluding that no effect exists. Medication reconciliation supported by information technology was an important tool for minimizing the percentage of medications with unintentional discrepancies